Rab‐E and its interaction with myosin XI are essential for polarised cell growth. Issue 4 (28th November 2020) - Orr, Robert G.; Furt, Fabienne; Warner, Erin L.; Agar, Erin M.; Garbarino, Jennifer M.; Cabral, Sarah E.; Dubuke, Michelle L.; Butt, Allison M.; Munson, Mary; Vidali, Luis
Summary: The fundamental process of polarised exocytosis requires the interconnected activity of molecular motors trafficking vesicular cargo within a dynamic cytoskeletal network. In plants, few mechanistic details are known about how molecular motors, such as myosin XI, associate with their secretory cargo to support the ubiquitous processes of polarised growth and cell division. Live‐cell imaging coupled with targeted gene knockouts and a high‐throughput RNAi assay enabled the first characterisation of the loss of Rab‐E function. Yeast two‐hybrid and subsequent in silico structural prediction uncovered a specific interaction between Rab‐E and myosin XI that is conserved between P. patens and A. thaliana . Rab‐E co‐localises with myosin XI at sites of active exocytosis, and at the growing tip both proteins are spatiotemporally coupled. Rab‐E is required for normal plant growth in P. patens and the rab‐E and myosin XI phenotypes are rescued by A. thaliana's Rab‐E1c and myosin XI‐K/E, respectively. Both PpMyoXI and AtMyoXI‐K interact with PpRabE14, and the interaction is specifically mediated by PpMyoXI residue V1422. This interaction is required for polarised growth. Our results suggest that the interaction of Rab‐E and myosin XI is a conserved feature of polarised growth in plants.